The enhancement of nodal properties in the dorsal visual pathway is associated with compensatory mechanisms of visuospatial cognitive abilities following total sleep deprivation - Han, Zhenyu; Gang, Zihan; Ma, Mengke; Shao, Yongcong (Frontiers in Neuroscience, 2025)
IntroductionVision is the most critical sensory perception in humans, however, total sleep deprivation (TSD) impairs visuospatial cognitive abilities. While evidence suggests that the brain actively counteracts the adverse effects of TSD to preserve visual cognition, the underlying neural mechanisms remain poorly understood.MethodsTo explore the compensatory mechanisms of TSD on visuospatial cognition, we collected resting-state electroencephalogram (EEG) data from 24 participants at baseline state (BS) and after 36 h of TSD, along with behavioral data from a mental rotation task. Graph theory-based analyses were employed to assess global and nodal network properties.ResultsBehaviorally, reaction time (RT) significantly increased under TSD compared to BS, indicating impaired spatial cognition. In contrast, accuracy (ACC) for mirrored 120° trials significantly improved under TSD, suggesting that participants invested greater effort in more demanding tasks and adopted a strategy of prolonged RT to maintain ACC. EEG findings revealed a significant increase in the small-worldness index (sigma) after TSD, which positively correlated with the improvement in ACC for mirrored 120° trials. Nodal properties in the dorsal visual pathway, particularly in parietal regions, were significantly enhanced following TSD. Similarly, nodal properties in the left middle frontal gyrus and left superior temporal gyrus were significantly strengthened, and these enhancements were positively associated with the increase of ACC in mirrored 120° trials.DiscussionThese results demonstrate that individuals compensate for TSD-induced visual cognitive deficits by enhancing small-world network property and information transfer efficiency in the dorsal visual pathway. Additionally, top-down control is mediated by the middle frontal gyrus, while bottom-up information integration is facilitated by the superior temporal gyrus.